Social Deconstruction of Discrimination Against Former Convicts in Wonomulyo, West Sulawesi - Masni, Masni; Hasnawi haris; Jumadi, Jumadi; Syamsu Andi Kamaruddin; Hamsu Abdul Gani (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
This study explores the social discrimination faced by former prisoners in Wonomulyo, Sulawesi Barat, and its impact on their reintegration into society. Social discrimination, fueled by negative perceptions and deep-rooted stereotypes, significantly hinders the ability of former inmates to adapt and contribute positively to their communities. The research highlights how local cultural norms, which emphasize social harmony and moral values, exacerbate the stigma attached to former prisoners, viewing them as threats to the community's well-being. The study reveals that this discrimination not only affects the individuals but also extends to their families, further isolating them from society. The findings also show that lack of societal understanding about the importance of reintegration, coupled with inadequate systemic support, creates barriers for former prisoners to access employment, build relationships, and regain self-esteem. The research concludes that a holistic approach is needed, involving community education, inclusive policies, and empowerment programs, to address the discrimination and support the successful reintegration of former prisoners. Such efforts will help shift the social construct from one of exclusion to one of acceptance and opportunity.